Perception of young employees on communicating and sharing working relationships with older employees in Higher Learning Institutions in Malaysia - Saodah Wok,; Junaidah Hashim, (Universiti Kebangsaan Malaysian, 2012)
This study investigates the perception of young employees (less than 40 years old) on their older counterparts (56-58 years old) pertaining to communicating and sharing working relationships. The main objective of the study is to analyze the perception of young employees on working relationships satisfaction with communicative teamwork, mutual learning, participative decision making, and communicating feedback of the older employees in higher learning institutions. A total of 575 employees in five Malaysian universities in the Klang Valley participated in the study. Survey research design was used for the study. Data were gathered using questionnaire and analyzed using SPSS WIN 16.0 for both descriptive and inferential statistics. Results indicated that, on the whole, young employees have positive teamwork relationships with the older employees. They learned a lot from the older employees as the older employees are helpful in sharing their experiences in decision making. At the same time, the young employees receive positive feedback from the older employees. However, the older employees hardly compliment the young employees for their achievements.